Essential Speech and Language Technology for Dutch: Results by the STEVIN-programme - Peter Spyns, Jan Odijk (Cham Springer Nature, 2013)
Computational Linguistics; Germanic Languages; Artificial Intelligence (incl. Robotics); Computing Methodologies
English
Keywords: The arts; Humanities; Computational Linguistics; Germanic Languages; Artificial Intelligence (incl. Robotics); Computing Methodologies